(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In this work, the application of the catalyst containing (MoO3)x∙(ZnO)y∙(ZrO2)z/HSZ in the catalytic aromatization of the propane-butane fraction was investigated. The experiments were carried out in a flow catalytic device in the stationary phase of the catalyst (catalyst volume 6 cm3), at 450-600 ℃, at normal atmospheric pressure (P = 0.1 MPa), under the volumetric rate of propane-butane fraction 400-600 h-1. As a result of the experiment, the best modifying additives were found Zn, Zr, Ga, and Mo. The conversion of propane begins at 450 ℃ and reaches 100%; where the total conversion of propane reaches 600 ℃. Aromatic hydrocarbons are formed in sufficient quantities at 500 ℃ and a maximum value of 52.5% is reached at 600 ℃. The conversion of butane to aromatic hydrocarbons is easier than propane. At 550 ℃ the yield of aromatic hydrocarbons is 47% while the conversion of butane is 100%.